Faktor yang Mempengaruhi Alih Fungsi Lahan Daerah Resapan Air Kecamatan Cimenyan - Bagas Wijayakusuma (Jurnal Riset Perencanaan Wilayah dan Kota, 2023)
Abstract. Many water catchment areas (DRA) have been converted into built-up areas, one of which is the Cimenyan District. Looking at the related problems, the authors argue that "Factors influencing the conversion of land functions in the Cimenyan Subdistrict Water Catchment Area as Part of the North Bandung Area (KBU)" need to be carried out. The purpose of the research was to find out the area of ​​the water catchment area and how much land has been converted to other uses and how to solve this problem because if the area and identify what factors make water catchment land in Cimenyan sub-district change its function from its designation. The method used is the mixed method using methods including literature studies, scientific journal interviews, observations, and also documentation which will later be analyzed using spatial methods and multiple linear regression analysis. From the research that has been carried out, the authors conclude that there is land use change. in the Cimenyan District water catchment area of ​​31.9 Ha which changed its designation to built-up land. There are 4 influencing factors, namely economic growth, population growth, population migration and facilities and infrastructure. Abstrak. Banyak Daerah Resapan Air (DRA) yang mengalami alih fungsi menjadi lahan terbangun salahsatunya daerah Kecamatan Cimenyan. Melihat permasalahan terkait maka penulis berpendapat bahwa “Faktor yang mempengaruhi Alih Fungsi Lahan Daerah Resapan Air Kecamatan Cimenyan Sebagai Bagian Dari Kawasan Bandung Utara (KBU)” perlu dilakukan. Tujuan penelitian yang diambil yaitu ingin mengetahui luasan kawasan resapan air dan berapa banyak lahan yang dialih fungsikan ke peruntukan lain dan bagaimana upaya untuk menyelesaikan permasalahan tersebut karena jika Kawasan dan mengidentifikasikan faktor apa saja yang membuat lahan resapan air di kecamatan cimenyan beralih fungsi dari peruntukan nya . Metode yang dipakai adalah mix method dengan menggunakan metode antara lain studi literatur, jurnal ilmiah wawancara, observasi, dan juga dokumentasi yang nanti nya akan dianalisis menggunakan metode spasial dan analisis regresi liner berganda .Dari penelitian yang telah di lakukan,penulis menyimpulkan adanya alih fungsi lahan pada kawasan resapan air Kecamatan Cimenyan sebesar 31.9 Ha yang berubah peruntukan menjadi lahan terbangun. Adanya alih fungsi lahan Kawasan Resapan Air di Kecamatan Cimenyan ini juga disebabkan oleh 4 faktor yang mempengaruhi, yaitu pertumbuhan ekonomi pertumbuhan penduduk, migrasi penduduk dan sarana dan prasarana. .